Genetic Drift and Purifying Selection Shaped Mitochondrial Genome Variation in the High Royal Jelly-Producing Honeybee Strain (Apis mellifera ligustica) - Ma, Chuan; Hu, Ruoyang; Costa, Cecilia; Li, Jianke (Frontiers in Genetics, 2022)
Mitochondrial genomes (mitogenomes) are involved in cellular energy metabolism and have been shown to undergo adaptive evolution in organisms with increased energy-consuming activities. The genetically selected high royal jelly-producing bees (RJBs, Apis mellifera ligustica) in China can produce 10 times more royal jelly, a highly nutritional and functional food, relative to unselected Italian bees (ITBs). To test for potential adaptive evolution of RJB mitochondrial genes, we sequenced mitogenomes from 100 RJBs and 30 ITBs. Haplotype network and phylogenetic analysis indicate that RJBs and ITBs are not reciprocally monophyletic but mainly divided into the RJB- and ITB-dominant sublineages. The RJB-dominant sublineage proportion is 6-fold higher in RJBs (84/100) than in ITBs (4/30), which is mainly attributable to genetic drift rather than positive selection. The RJB-dominant sublineage exhibits a low genetic diversity due to purifying selection. Moreover, mitogenome abundance is not significantly different between RJBs and ITBs, thereby rejecting the association between mitogenome copy number and royal jelly-producing performance. Our findings demonstrate low genetic diversity levels of RJB mitogenomes and reveal genetic drift and purifying selection as potential forces driving RJB mitogenome evolution.